2015
DOI: 10.5539/jfr.v4n4p38
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Baru Almond and Brazil Nut Against Hyperlipidemia and Oxidative Stress In Vivo

Abstract: <p>This study evaluated the effect of baru (<em>Dipteryx alata </em>Vog.) almond, an edible seed native from Brazilian Savanna, and Brazil nut (<em>Bertholletia excelsa</em> H. B. K.) on serum lipid profile and hepatic lipid peroxidation in rats fed high-fat diets. Four groups of eight young adult male Wistar rats were treated for nine weeks with one of the following diets: high-fat diets - 0.1% colic acid + 1% cholesterol + 5% lard + 15% of lipid from lard, baru almond or Brazil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 32 publications
2
27
0
7
Order By: Relevance
“…Brazil nut stands out with almost 60% lipids, whereas the other nuts contain approximately 45% lipids. This finding is consistent with that found by other authors in different nuts 1,4,5,10 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Brazil nut stands out with almost 60% lipids, whereas the other nuts contain approximately 45% lipids. This finding is consistent with that found by other authors in different nuts 1,4,5,10 .…”
Section: Discussionsupporting
confidence: 94%
“…The predominance of polyunsaturated fatty acids in the Brazil nut, approximately 50%, was also observed in other studies 5,10 . It is worth adding that the tendency of polyunsaturated fatty acids to undergo oxidation is higher than that of monounsaturated fatty acids; thus, the Brazil nut is more vulnerable to oxidation.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Consumption of baru almonds also reduces adiposity and improves the lipid profile in women with overweight and obesity (SOUZA, 2014). Therefore, this type of food can be beneficial in the current nutritional and epidemiological transition phase experienced by the Brazilian population, who consume a large amount of saturated fat -and carbohydrate-rich foods (FERNANDES et al, 2015) and have a high obesity prevalence. To further investigate the potential of this food, the present study analyzed the effect of baru almond consumption on the body weight, visceral fat (percent adiposity, amount of adipose tissue) and blood levels (such as triglycerides, total cholesterol, and glucose) in Swiss mice with diet-induced obesity.…”
Section: Consumo De Amêndoa De Baru (Dipteryx Alatamentioning
confidence: 99%
“…In the group fed with HGBA diet, the negative effect of diet HG was; however, attenuated by the consumption of baru flour, confirming studies conducted with other almonds (CHOUDHARY et al, 2009). In addition, FERNANDES et al (2015) showed that the serum levels of total cholesterol and triglycerides in Wistar rats treated with baru almonds are lower than those in animals fed lard. Other studies showed that diet supplementation with baru almonds improved the serum lipid levels in moderately hypercholesterolemic individuals, and recommended this food to prevent cardiovascular diseases (BENTO et al, 2014).…”
mentioning
confidence: 99%